The Lower Bounds of Eigenvalues by the Wilson Element in Any Dimension (Advances in Applied Mathematics and Mechanics, 2011)
In this paper, we analyze the Wilson element method of the eigenvalueproblem in arbitrary dimensions by combining a new technique recentlydeveloped in [10] and the a posteriori error result. Weprove that the discrete eigenvalues are smaller than the exact ones.